Self-expression and discourse continuity in a multilevel EUD environment: The case of moodle. (June 2017) - da Silveira Espindola, Luciana; Selbach Silveira, Milene
Abstract: The search for ways to empower end users in activities such as programming and application customization has been subject of great effort among the research community, leading to the development of EUD environments, proper for end user's activities. Among such environments there are the ones that have multiple layers of (distinct) users, consequently allowing multiple customizations. As an example, we have the Virtual Learning Environments (VLEs), with focus on education. In the particular case of VLEs, we are interested in verifying the discourse continuity after multiple customizations by many users, looking at how it impacts on teacher's self-expression at the end of this chain, and how this expression is perceived by the students while interacting with the product of their teacher's effort. This is part of a qualitative and descriptive evaluation with theoretical fundamentals on the Semiotic Engineering theory, the self-expression phenomenon, and end-user development practices. We have conducted three studies using Moodle as the VLE of choice. The first one identified three ways by which teachers practice self-expression via Moodle: through written language, interface customization, and expression through content, and Study 2 revealed that students perceive these same ways of expression. Finally, the inspections and the analyses of the interviews and questionnaires applied during Study 3 have confirmed these results, even after many customizations. That is, the teacher's self (e.g., personality) is present and recognizable via interface. By taking EUD under the perspective of the Semiotic Engineering theory and self-expression, we were able to study the metacommunication intrinsic to multilevel customization software such as Moodle.